Time-Average Heat Transfer Coefficient for Steam-Air Condensation during the Dropping of Containment Pressure - Shaodan Li; Kai Hui; Zhiwu Ke; Yong Li (Energies, 2022)
The passive containment cooling system (PCCS) has been applied in the new generation nuclear power plant. Previous studies mainly focused on steady-state heat transfer, but the actual heat transfer of PCCS is the transient process. Thus, investigating the transient heat transfer during the containment pressure dropping is necessary. The present study proposes a time-average condensation heat transfer coefficient (time-average condensation HTC) to characterize the intensity of transient condensation heat transfer. The time-average condensation HTC is defined as the heat absorbed per unit heat transfer area and per unit wall subcooling in a unit time. Experiments were performed to research the effect of initial gas-mixture pressure and air mass fraction on transient HTC. The result showed that the more significant gas-mixture pressure and lower air mass fraction could promote the transient-state heat transfer, especially the low air mass fraction. Based on the experimental result, a detailed empirical correlation for the time-average heat transfer coefficient is developed with an error of ±20%. Another simplified empirical correlation that only includes air mass fraction is also proposed to predict the transient heat transfer roughly. Besides, research on self-sustaining stability is also conducted to evaluate the stable operation characteristic of PCCS. The system can respond quickly and then run to a new steady state after interference during the long-term operation of PCCS. The phenomenon above implies that PCCS has good self-sustaining stability.